PENGEMBANGAN BUKU RAMAH CERNA BERMUATAN NILAI BERNALAR KRITIS KATEGORI PEMBACA B2 DI SEKOLAH DASAR - Ginardi, Ilma Vitaloka; Aryanto, Sani (Journal of Professional Elementary Education, 2024)
Literacy is a means that is needed by every individual, this is because literacy is needed to keep up with the times. However, as is known, the literacy rate in Indonesia tends to be low. Digest-friendly books are suggestions that can be used and are believed to be a solution in improving literacy in early childhood, especially at the elementary school level. Therefore, the purpose of this study is to provide a comprehensive overview in the process of developing a digestible book that contains the value of the Pancasila Student Profile and contains the critical reasoning value of the B2 early reader category in elementary school. The research uses a Research and Development (R&D) research design through the ADDIE development model, including five steps, namely Analysis Design, Development, Implementation, and Evaluation. The target of this research is grade 1 elementary school with a total of 25 people at SDN Margahayu V, Bekasi City. This research was carried out by filling out questionnaires and implementing digestible books using workshop sheets as assessments and the use of digestible books to make it easier for teachers to teach and develop children's ability to reason critically. However, the results of this study are considered successful in developing a digestible book that makes it easier for teachers in the process of teaching early literacy and is categorized as very good with a percentage of 88%.